RADIATION DOSE TO MALDIVIANS VIA THE CONSUMPTION OF TUNA FISH CAUGHT FROM THE COASTAL WATERS OF INDIAN OCEAN. Issue 3 (29th April 2019) - Nadhiya, Aishath; Khandaker, Mayeen Uddin; Mahmud, Sultan; Yarima, Mudassir Hassan
Abstract: Recognising the consumption of tuna fish as a major foodstuff in Maldivian diet, the presence of naturally occurring radionuclides in Yellowfin and Skipjack tuna are determined by using HPGe gamma-ray spectrometry to evaluate the health hazards to Maldivians. The samples were collected from different atolls of Maldives adjacent to the coastal waters of Indian Ocean. The activity concentrations (Bq kg −1 ) in Yellowfin tuna for 226 Ra, 232 Th and 40 K are in the ranges of 4.2 ± 1.8–10.5 ± 1.1, 1.3 ± 0.3–3.2 ± 0.7 and 589 ± 29–697 ± 34, respectively while in Skipjack tuna the respective ranges are 3.9 ± 0.5–13.2 ± 1.1, 1.3 ± 0.3–2.7 ± 0.6 and 511 ± 28–681 ± 35. The committed effective dose (mean 263 μSv y −1 ) received by an individual due to the dietary intake of Yellowfin tuna falling below the UNSCEAR referenced global internal dose limit of 290 μSv y −1 ; while for Skipjack tuna, the estimated dose (mean 365 μSv y −1 ) exceeds the world average limiting value. The carcinogenic risk was found to be well below the ICRP referenced acceptable limit of 2.5 × 10 −3 . The present study indicates that the radiation dose to Maldivian via the consumption of Yellowfin tuna poses an insignificant threat to the public health. However, prolonged consumption of Skipjack tuna fish from the studied areas may pose a cumulative risk to the public health.